TINGKAT RESILIENSI REMAJA YANG ORANG TUANYA BERCERAI - Afdhal; Taufik; Miftahul Fikri; Fikriyah Mardhatillah; Frischa Meivilona Yendi (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Resilience in adolescents experiencing parental divorce is influenced by gender and the type of divorce. Boys and girls exhibit different responses to divorce, both behaviorally and emotionally. Additionally, the type of divorce (divorce alive or divorce dead) has varying impacts on adolescent resilience. The respondents of this study were 87 adolescents selected using purposive sampling. The instrument used was a resilience questionnaire. Data were analyzed using descriptive statistical techniques and t-test analysis. The results show: (1) The overall level of resilience among adolescents is mostly in the moderate category; (2) There is a significant difference in resilience between male and female adolescents; (3) There is a significant difference in resilience between adolescents experiencing parental divorce in the case of divorce alive versus divorce dead. To support optimal resilience development, it is important for teachers, counselors, and parents to understand these dynamics and provide support that meets the individual needs of adolescents.